Revisiting the farm size-productivity relationship based on a relatively wide range of farm sizes: Evidence from Kenya - Muyanga, Milu; Jayne, Thomas S. (Wiley, 2019)
This paper revisits the inverse farm size-productivity relationship in Kenya. The study makes two contributions. First, the relationship is examined over a much wider range of farm sizes than most studies, which is particularly relevant in Africa given the recent rise of medium- and large-scale farms. Second, we test the inverse relationship hypothesis using three different measures of productivity including profits per hectare and total factor productivity, which are arguably more meaningful than standard measures of productivity such as yield or gross output per hectare. We find a U-shaped relationship between farm size and all three measures of farm productivity. The inverse relationship hypothesis holds on farms between zero and 3 hectares. The relationship between farm size and productivity is relatively flat between 3 and 5 hectares. A strong positive relationship between farm size and productivity emerges within the 5 to 70 hectare range of farm sizes. Across virtually all measures of productivity, farms between 20 and 70 hectares are found to be substantially more productive than farms under 5 hectares. When the analysis is confined to fields cultivated to maize (Kenya’s main food crop) the productivity advantage of relatively large farms stems at least partially from differences in technical choice related to mechanization, which substantially reduces labor input per hectare, and from input use intensity.